A Late Postclassic (ca. AD 1350–1521) Border Shrine at the Site of Tayasal, Petén, Guatemala. Issue 1 (27th March 2019) - Halperin, Christina T.; Hruby, Zachary X.
Abstract : Shrines were a regular component of ceremonial architecture in the public plazas of Postclassic Maya centers. Small shrines and natural landmarks such as caves and outcrops at the borders of settlements or in wilderness locations also served, and in some cases continue to serve, as important ritual loci for Maya peoples. These more peripheral locales were not only critical access points to the supernatural, but also served to delineate places. Because these border features, which represent only a given moment in a constantly shifting social and political landscape, are sometimes unmodified or are inconspicuous, they are relatively ephemeral and difficult to identify in the archaeological record. This paper documents a Late Postclassic shrine paired with a natural feature, a small hill, from the site of Tayasal in Petén, Guatemala. We argue that it served as a border shrine. Paired with the small hill, the two embodied a liminal frontier, not only between earthly and spiritual realms but also between settled and unsettled space. Abstract : Los santuarios eran un componente regular de la arquitectura ceremonial en las plazas públicas de los centros mayas del Posclásico. Sin embargo, los santuarios pequeños y ciertos rasgos naturales del paisaje, como cuevas y afloramientos en las orillas de los asentamientos o en lugares alejados de los mismos, también sirvieron y, en algunos casos, siguen sirviendo como importantes sitios rituales para los Mayas. Estos espacios periféricos no solo eran puntos de acceso a lo sobrenatural, sino que también servían para demarcar lugares. Debido a que estos rasgos fronterizos representan solo un momento en un paisaje social y político en cambio constante, a veces no están modificados, o son discretos, efímeros y, en consecuencia, difíciles de identificar arqueológicamente. Este artículo documenta un santuario del Posclásico tardío asociado a un rasgo natural, un pequeño cerro, del sitio de Tayasal en Petén, Guatemala. Argumentamos que funcionó como un santuario fronterizo y que, junto con el pequeño cerro, revelaba una frontera liminal no solo entre los espacios terrenales y espirituales, sino también entre espacios poblados y no poblados.